2013
DOI: 10.1186/2001-1326-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Proposed roadmap to stepwise integration of genetics in family medicine and clinical research

Abstract: We propose A step‐by‐step roadmap to integrate genetics in the Electronic Patient Record in Family Medicine and clinical research. This could make urgent operationalization of readily available genetic knowledge feasible in clinical research and consequently improved medical care. Improving genomic literacy by training and education is needed first. The second step is the improvement of the possibilities to register the family history in such a way that queries can identify patients at risk. Adding codes to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…These findings contribute to studies demonstrating the value of educational interventions in hereditary cancer (Blazer et al 2004;Carroll et al 2009Carroll et al , 2011Houwink et al 2013Houwink et al , 2014aSchroy et al 2005;Watson et al 2001). Watson showed improved referral decisions for patients with a FH of breast/ovarian cancer, using mailed information including a laminated summary card with simple referral guidelines, a booklet with more detailed information, and two patient leaflets (Watson et al 2001).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…These findings contribute to studies demonstrating the value of educational interventions in hereditary cancer (Blazer et al 2004;Carroll et al 2009Carroll et al , 2011Houwink et al 2013Houwink et al , 2014aSchroy et al 2005;Watson et al 2001). Watson showed improved referral decisions for patients with a FH of breast/ovarian cancer, using mailed information including a laminated summary card with simple referral guidelines, a booklet with more detailed information, and two patient leaflets (Watson et al 2001).…”
Section: Discussionmentioning
confidence: 54%
“…Houwink showed that an online genetics Continuing Professional Development module resulted in sustained improvement of genetics knowledge in general practitioners. (Houwink et al 2013). However, skills such as referral to a specialist and knowledge of benefits and limitations of genetic testing did not improve significantly.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We propose a strategic integration framework that includes the following elements: ensuring the fit of genomic medicine with the key approach of whole-person care through personalization; targeting areas that will see early benefit such as pharmacogenomics; ensuring that appropriate clinical decision support is available that supplements any education efforts for primary care providers; assessing the economic impact of genomic medicine to determine optimal implementation; supplementing genomic information with patient information including the full FHH; and looking to the future for areas of development such as the intersection of public health, primary care and genomics. Our strategic framework builds on early work that emphasizes the role of education and step-wise implementation [18,20,21,89]. Effective ways to continuously review and summarize the rapidly accumulating complex knowledge are needed to facilitate policy decisions and evidence-based recommendations [88].…”
Section: Future Perspectivementioning
confidence: 99%
“…Houwink and colleagues proposed a roadmap for stepwise integration of family history data with primary care and genomic services based upon the Dutch research experience, which provides a useful illustration for primary practices and health care centers undergoing clinical implementation. 43 Emery and colleagues, in the United Kingdom and Australia, have already shown that combining primary care education, partnership models, and systematic integration of the family history within EHRs is effective in improving hereditary cancer screening. 21,38 Finally, multiple US health care systems-including the Cleveland Clinic, Duke University Medical Center, Intermountain Healthcare, Vanderbilt University Medical Center, and St. Jude Children's Research Hospital-have successfully integrated family history and genomic medicine within EHRs.…”
Section: Clinical Implementation and Evaluationmentioning
confidence: 99%